EP260 Is there still a role for laparoscopic radical hysterectomy? Personalizing surgical approach in early stage cervical cancer. (1st November 2019) - Pedone Anchora, L; Bizzarri, N; Capozzi, VA; Gallotta, V; Chiantera, V; Cosentino, F; Lombisani, A; Scambia, G; Ferrandina, G
Abstract : Introduction/Background: To compare survival outcomes of laparoscopic and open surgery for radical hysterectomy (RH) among patients with early-stage cervical cancer (CC) and to identify which subgroups may benefit from one approach rather than the other. Methodology: 237 and 303 consecutive patients, with clinical FIGO stage from IA1 with lymph vascular space involvement to IB1/IIA1 CC underwent open and laparoscopic RH respectively in 3 Italian Institutions. Differences in terms of progression-free survival (PFS) between the two surgical approaches were tested in the entire population and in different patient's subgroups. Results: Median follow up was 34 months. Open and laparoscopy procedures had similar 3-yr PFS rate in the entire series (86.4% vs 85.6%, p=0.987). PFS of the two approaches were compared among subgroups stratified by tumor histology, tumor grading, tumor diameter, lymph vascular space status, parametrial invasion, lymph node status and adjuvant treatment.Open and laparoscopic approaches revealed a significantly different 3-yr PFS rate only among patients with >20 mm tumor (85.2% vs 69.2% respectively, p=0.026). On the contrary 3-yr PFS in ≤2 cm tumor did not differ between open and laparoscopic surgery (87.5% vs 93.4% respectively, p=0.151). Conclusion: Tumor diameter could be considered the most important determinant to choosing to guide the choice of surgical approach in early stage CC. Women with >20 mm disease should undergo open RH. In case of tumor ≤20 mm, both of the approaches appear to be safe. Therefore, laparoscopic surgery could still be considered an option in this subgroup of patients. Disclosure: Nothing to disclose.